PESTABLISHING NATIONAL CHARACTER THROUGH HISTORY LEARNING IN GLOBALIZATION VILLAGE - Patricia Blosser; Ghiatau Thompson (SENSEI RESEARCH CENTER, 2021)
This research is based on the occurrence of the COVID-19 pandemic. The purpose of Character education is an important part that cannot be ignored, it needs a serious and systematic approach as an effort to maintain the values of national nationalism which of course are increasingly fading due to the swift currents of globalization. Through history education, national values are instilled in every process of learning history so that history is taught not only as a lesson about the past and stops in the past but is also able to provide inspiration, ideas for the younger generation to realize the importance of nationalism and a sense of pride in their homeland. and work according to the times for the progress of the Indonesian nation. Globalization has penetrated into various aspects of life, political, economic, social and cultural as well as increasingly sophisticated technology is a necessity that must be accepted.